A Guide for Volunteer Organizations to Assess Risk - Matthew Benge (EDIS)
Volunteer organizations help communities in a variety of ways, and volunteers serve in various capacities relating to projects, goals, and tasks. With these varying roles, there are possible risks that volunteers, clients, and the organization can encounter. Risk management is a tool that many volunteer organizations and volunteer leaders should consider when thinking of the safety and protection of their organization and its volunteers. This new 4-page publication of the UF/IFAS Department of Agricultural Education and Communication provides a brief guide to the risk management model. Written by Matt Benge. https://edis.ifas.ufl.edu/wc414